A new species of Coryphophylax Fitzinger in: Steindachner, 1867 (Sauria: Iguania: Agamidae) from the Andaman Islands, India - Harikrishnan, S.; Vasudevan, Karthikeyan; Chandramouli, S. R.; Choudhury, B. C.; Dutta, Sushil Kumar; Das, Indraneil (Zootaxa, 2012)
The systematic position of the agamid genus Coryphophylax (Squamata: Agamidae) is given as monotypic and endemicto the Andaman and Nicobar Islands in the Bay of Bengal, India. After having surveyed intensively in thirteen differentIslands and examined several individuals in the Andamans group of islands, we describe a second species ofCoryphophylax from the lowland rainforests of the South Andaman Island. Coryphophylax brevicaudus sp. nov. isdifferentiated from its congener, C. subcristatus (Blyth, “1860” 1861) by its smaller size, relatively shorter tail, presenceof nuchal and dorsal crests in both sexes, midbody scale row counts and colour pattern. The new species lives in sympatrywith C. subcristatus. The taxonomic history and systematic status of the genus Coryphophylax are discussed, and the need for continued surveys in the Islands is emphasized.